1967
DOI: 10.1017/s0016672300010600
|View full text |Cite
|
Sign up to set email alerts
|

Two-way selection for body weight in Tribolium on two levels of nutrition

Abstract: Parameters necessary for predicting direct and correlated responses for large and small 13-day larval weight in T. castaneum on two levels of nutrition were estimated in the base population. Larval weight in the GOOD environment was approximately twice that observed in POOR. Heritabilities (estimated from the ratio of sire component to total phenotype variance) of larval weight on the two rations were similar, 0·21 ± 0·06 and 0·19 ± 0·05 for GOOD and POOR, respectively. Heritabilities based on dam-offspring co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1
1

Year Published

1967
1967
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 17 publications
4
13
1
1
Order By: Relevance
“…These data suggest that the protein requirement of the T line quail has been reduced below levels of both the unselected control and also the P line, which has been selected on a high 28% CP diet. These results support the hypothesis (Hardin and Bell, 1967) that for maximum performance under a single environment, selection should be practiced under that environment, because T line quail had superior BW on the 18% CP diet and P line quail had superior BW on the high (27 to 30% CP) diets. Less clear in this particular study involving only protein level of the diet is the suggestion that for best allaround performance, selection should be practiced under the worst rather than the best environment (Falconer, 1960).…”
Section: Experiments 2 (Generation 79)supporting
confidence: 84%
See 1 more Smart Citation
“…These data suggest that the protein requirement of the T line quail has been reduced below levels of both the unselected control and also the P line, which has been selected on a high 28% CP diet. These results support the hypothesis (Hardin and Bell, 1967) that for maximum performance under a single environment, selection should be practiced under that environment, because T line quail had superior BW on the 18% CP diet and P line quail had superior BW on the high (27 to 30% CP) diets. Less clear in this particular study involving only protein level of the diet is the suggestion that for best allaround performance, selection should be practiced under the worst rather than the best environment (Falconer, 1960).…”
Section: Experiments 2 (Generation 79)supporting
confidence: 84%
“…However, Hardin and Bell (1967) suggested that for maximum performance in a single environment, selection should be practiced under that environment. Therefore, the question of identifying the best selection environment may be dependent on a variety of objectives and other considerations.…”
Section: Introductionmentioning
confidence: 99%
“…These experiments were designed mainly to observe the response of a population under selection in a constant environment and then subsequently to test the product of selection in several different environments (Falconer, 1960;Druger, 1962;Hardin and Bell, 1967;Jinks andConnolly, 1973, 1975). In general, the results of these experiments showed that the greatest mean 237 response over a variety of environments came from selection for performance in the least favourable environment.…”
Section: Introductionmentioning
confidence: 99%
“…The observed correlated response in "poor" suggests a relatively large positive genetic correlation between larval weight in the two environments. (Hardin and Bell, 1967 estimated this genetic correlation to be o6o+o21 for this same base population.) From generation 4. to 30 the correlated response in "poor" was essentially zero even though response continued in the "good" environment until about generation i 2.…”
Section: Discussionmentioning
confidence: 91%